Fluorinated silicone rubber with controllable molecular weight and preparation method thereof

By using boron-containing organic bases as catalysts, the problems of difficult molecular weight control, high ring structure content, and poor storage stability in the preparation of fluorosilicone rubber are solved, and the preparation of high-quality and stable fluorosilicone rubber is achieved.

CN119350623AActive Publication Date: 2025-01-24DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411580389.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-24
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

In the existing fluorosilic rubber preparation technology, there are problems such as difficulty in controlling molecular weight, high ring structure content in polymer products, and poor storage stability due to metal residues of polymers.

Method used

A boron-containing organic base is used as a catalyst, and a boron-containing alkaline composition prepared by reacting with an alkali metal compound and a borane compound is used as a catalyst for the ring-opening polymerization of cyclosiloxane. The catalyst has good solubility and steric hindrance control capabilities, which reduces side reactions during the polymerization process.

Benefits of technology

The molecular weight controllability of fluorine silicon rubber is reduced, the content of the ring structure is reduced, the storage stability problem caused by metal residues is avoided, and the quality and stability of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350623A_ABST
    Figure CN119350623A_ABST
Patent Text Reader

Abstract

The invention provides fluorosilicone rubber with controllable molecular weight and a preparation method thereof, and belongs to the technical field of catalysis for preparing fluorosilicone rubber. Firstly, 1, 3, 5-trimethyl-1, 3, 5-tri (3, 3, 3-trifluoropropyl) cyclotrisiloxane and cyclosiloxane monomers are added into a polymerization reaction kettle to be heated and vacuumized for dehydration treatment, and the addition amount of the cyclosiloxane monomers accounts for 0.5%-20% of the total mass of the monomers. And adding the boron-containing alkaline composition into the polymerization reaction kettle, and polymerizing for 10-600 minutes at the temperature of 60-120 DEG C to prepare the fluorinated silicone rubber. According to the invention, the boron-containing alkaline composition is creatively used as a catalyst for ring-opening polymerization of cyclosiloxane, so that the flowability of the boron-containing alkaline composition is greatly improved; the side reaction in the polymerization process can be effectively inhibited; the prepared fluorinated silicone rubber can meet the use stability in high and low temperature environments without a special neutralization process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorosilicone rubber preparation catalyst, and relates to a fluorosilicone rubber raw rubber with controllable molecular weight suitable for industrialization and a preparation method thereof. Technical Background

[0002] The main chain structure of fluorosilicone rubber is mainly composed of -Si-O- repeating units with high flexibility and high bond energy, which gives it excellent high and low temperature resistance. The side chain is composed of trifluoropropyl (-CH2-CH2-CF3) and methyl (-CH3), and the fluorine-containing substituent significantly improves the material's tolerance to oils and solvents. Fluorosilicone rubber can therefore remain stable in extreme temperature conditions (-55℃~230℃) and oily environments. Its application areas include national defense and military industry, aerospace, deep-sea exploration, automobiles and petrochemicals, etc. It is one of the synthetic rubbers with the best comprehensive performance in the world.

[0003] In the production process of fluorosilicone rubber, the control of molecular weight is crucial, which directly affects the mechanical properties of the rubber and the quality of the final product. The catalysts commonly used in the preparation process, such as alkali metal hydroxides, quaternary ammonium hydroxides and quaternary phosphonium hydroxides, are all strongly alkaline. The strong electronic attraction of the fluorine side group increases the electrophilicity of the silicone bond, which triggers the "bite-back" within the molecule and the chain transfer side reaction between molecules during the polymerization process, resulting in a decrease in molecular weight and uneven distribution, and then generating a large amount of low molecular weight polymers. For example, when potassium hydroxide is used to perform bulk ring-opening polymerization on 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane (D3F), the average content of the ring body at the polymerization equilibrium state can be as high as 86.5% (Journal of Polymer Science Polymer Letter Edition, 1965, 3, 473-482).

[0004] To solve these problems, two main strategies are currently used. The first is to change the catalytic system, such as using less active butyl lithium as a catalyst and using dimethyl sulfoxide as a promoter to effectively inhibit the "backbite" reaction, thereby reducing the content of the ring body at the polymerization equilibrium (Journal of Polymer Science Part A, 1989, 27 (4), 1241-1258). Although the side reactions can be reduced to a certain extent by adjusting the auxiliary agent and the catalyst, the occurrence of side reactions has not been completely inhibited, which may eventually affect the quality of fluorosilicone rubber. The second is to control the polymerization reaction time and terminate the reaction when the yield of the linear polymer is the highest (CN 114381001 A). This requires higher control over the polymerization process and equipment, and may also lead to a decrease in the stability of the product batch. In addition, at the end of the polymerization, the problem of catalyst neutralization must be solved. The residual catalyst may attack the silicone bond in the polymer chain, resulting in chain breakage. In view of the high viscosity and excellent oil and chemical resistance of high molecular weight fluorosilicone rubber, the addition and effective dispersion of neutralizers are particularly difficult. Therefore, special measures must be taken during the preparation process to ensure the high performance and safety of the product. Summary of the invention

[0005] The present invention aims to solve the shortcomings of the existing fluorinated cyclosiloxane anionic ring-opening polymerization catalytic technology, including the difficulty in controlling the molecular weight, the high content of the ring structure in the polymerization product, the poor storage stability of the polymer due to metal residues, and the like. A boron-containing organic base is selected as a catalyst to provide a method for preparing fluorosilicone rubber with controllable molecular weight.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] First, the present invention provides a method for preparing fluorosilicone rubber, comprising the following steps:

[0008] In the first step, 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane and cyclosiloxane monomers are added into a polymerization reactor, heated and vacuumed for dehydration; wherein the amount of cyclosiloxane added accounts for 0.5%-20% of the total weight of the monomers.

[0009] In the second step, the boron-containing alkaline composition is added into the polymerization reactor, the amount of the boron-containing alkaline composition (calculated as the corresponding alkali metal hydroxide) is 8-500 ppm, and the polymerization reaction is started by heating to 60-120 degrees Celsius, and the polymerization is carried out for 10-600 minutes to prepare fluorosilicone rubber.

[0010] Furthermore, in the second step, the boron-containing alkaline composition is prepared by reacting an alkali metal compound with a borane compound, and the specific method is as follows: under the protection of an inert gas, an alkali metal compound is first added to the configuration kettle, and then the borane compound is slowly added at -40-60 degrees Celsius, and aged for 10-120 minutes to obtain a boron-containing alkaline composition with an alkali metal concentration of 0.1-1.0M, which is a transparent solution. The reaction principle process of this step is: a borane compound with Lewis acidity can form a complex with an organic base compound with Lewis basicity. These complexes have good solubility in both non-polar and polar solvents, which is convenient for adding materials, and by selecting borane compounds with different substituents, the steric hindrance around the oxygen anion activity can be effectively controlled, which helps to reduce the attack of the oxygen anion active center on the silicone bond in the larger polymer chain, thereby effectively inhibiting side reactions during the polymerization process.

[0011] Furthermore, in the second step, in the boron-containing alkaline composition, the molar ratio of the alkali metal compound to the borane compound is 1:(0.2-10), preferably 1:(1-3).

[0012] Furthermore, in the second step, the alkali metal compound is selected from lithium hydride, sodium hydride, potassium hydride, lithium hydroxide, sodium hydroxide, potassium sodium hydroxide, lithium tert-butoxide, sodium tert-butoxide, potassium tert-butoxide, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, phenyl lithium, lithium silicate, sodium silicate, potassium silicate, preferably n-butyl lithium.

[0013] Furthermore, in the second step, the borane compound is selected from trimethylboron, triethylboron, tri-n-butylboron, tri-sec-butylboron, trioctylboron, triphenylboron, tri(pentafluorophenyl)boron, preferably triethylboron and triphenylboron.

[0014] Furthermore, in the second step, the borane compound needs to be configured into a solution before use for easy operation, and the solvent can be at least one of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, acetone, 1,4-dioxane, methyl pyrrolidone, phosphazene base P4-t-Bu, tetrahydrofuran, methyl formate, ethyl acetate, toluene, diethylene glycol dimethyl ether, and ethylene glycol dimethyl ether, and prepared into a 0.1-1.0M solution.

[0015] Furthermore, the cyclosiloxane monomer is one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and 2,4,6-triphenyl-2,4,6-trimethylcyclotrisiloxane, preferably 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane.

[0016] A fluorosilicone rubber is prepared by the above-mentioned preparation method, and the structural formula of the fluorosilicone rubber is:

[0017]

[0018] Wherein, R is one or more of methyl, phenyl and vinyl, preferably methyl and vinyl;

[0019] Furthermore, the molecular weight of the fluorosilicone rubber is 0.2-3 million, and the molecular weight distribution is less than 1.50.

[0020] Beneficial effects of the present invention:

[0021] (1) In the process of preparing fluorosilicone rubber of the present invention, a boron-containing alkaline composition is innovatively used as a catalyst for the ring-opening polymerization of cyclosiloxane. The catalyst is a transparent solution, and a borane compound with Lewis acidity can form a complex with an organic base compound with Lewis basicity. These complexes have good solubility in both non-polar and polar solvents. Compared with traditional cyclosiloxane catalysts such as alkali rubber, its fluidity is greatly improved, which facilitates the feeding operation in industrial production.

[0022] (2) Based on the method provided by the present invention, by selecting borane compounds with different substituents, the steric hindrance around the oxygen anion active center can be effectively controlled. This helps to reduce the attack of the oxygen anion active center on the silicone bond in the larger polymer chain, thereby effectively inhibiting the side reactions during the polymerization process.

[0023] (3) This catalytic system can maintain the good storage stability of fluorosilicone rubber without the need for an additional neutralization process. This is mainly due to the introduction of borane compounds. Boron elements can form a buffer system with alkali metals, greatly reducing the catalytic effect of alkali metals in the rubber matrix. Therefore, the fluorosilicone rubber prepared by this catalytic method can meet the stability requirements for use in high and low temperature environments without the need for a special neutralization process. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The thermal weight loss curves of the fluorosilicone rubber prepared in Example 18 of the present invention and Comparative Example 15 are shown. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with embodiments.

[0026] Examples 1-14 are methods for preparing boron-containing alkaline compositions, and the main preparation parameters are shown in Table 1. The alkali metal concentration is measured by ICP-OES method (the measurement parameters are: the metered catalyst sample is sintered at 450° C. for 5 hours, and then acidified with water after cooling, and the treated sample is dissolved in water for ICP test).

[0027] Table 1

[0028]

[0029]

[0030] The specific implementation methods of Examples 1-14 are as follows:

[0031] Example 1

[0032] 9.5 ml of tetrahydrofuran was added to a 100 ml reactor, and 0.01 g of lithium hydride (1.0 mmol) and 0.5 ml of triethylborane (1.0 M, 0.5 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to -40 degrees Celsius and maintained for 120 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.100 M.

[0033] Example 2

[0034] 9.0 ml of acetonitrile was added to a 100 ml reactor, and 0.02 g of sodium hydride (1.0 mmol) and 1.0 ml of tri-n-butylboron (1.0 M, 1.0 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to -20 degrees Celsius and maintained for 100 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.100 M.

[0035] Example 3

[0036] 2.2 ml of dimethyl sulfoxide was added to a 100 ml reactor, and 0.05 g of potassium hydride (1.2 mmol) and 7.8 ml of trioctyl boron (1.0 M, 7.8 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to 0 degrees Celsius and maintained for 80 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.120 M.

[0037] Example 4

[0038] 6.5 ml of N,N-dimethylformamide was added to a 100 ml reactor, and 0.07 g of sodium hydroxide (1.7 mmol) and 3.5 g of triphenylboron (14.3 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually raised / lowered to 20 degrees Celsius and maintained for 60 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.168 M.

[0039] Example 5

[0040] 4.3 ml of pyridine was added to a 100 ml reactor, and 0.12 g of lithium tert-butoxide (1.8 mmol) and 5.6 g of tris(pentafluorophenyl)boron (10.9 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually raised to 40 degrees Celsius and maintained for 40 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.182 M.

[0041] Example 6

[0042] 6.4 ml of acetone was added to a 100 ml reactor, and 0.10 g of sodium tert-butoxide (1.0 mmol) and 3.5 ml of trimethylboron (1.0 M, 3.5 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually raised to 60 degrees Celsius and maintained for 10 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.101 M.

[0043] Example 7

[0044] 2.3 ml of 1,4-dioxane was added to a 100 ml reactor, and 0.17 ml of potassium tert-butoxide (1.5 mmol) and 7.5 ml of tri-n-butylboron (1.0 M, 7.5 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to -40 degrees Celsius and maintained for 120 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.150 M.

[0045] Example 8

[0046] 1.2 ml of methylpyrrolidone was added to a 100 ml reactor, and 0.17 ml of n-butyl lithium (0.01 M, 1.7 mmol) and 8.7 ml of trioctyl boron (1.0 M, 8.7 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to -20 degrees Celsius and maintained for 100 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.173 M.

[0047] Example 9

[0048] 9.4 ml of phosphazene base was added to a 100 ml reactor, and 0.11 ml of sec-butyl lithium (0.01 M, 1.1 mmol) and 0.5 g of triphenylboron (2.2 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to 0 degrees Celsius and maintained for 80 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.111 M.

[0049] Example 10

[0050] 7.8 ml of methyl formate was added to a 100 ml reactor, and 0.13 ml of tert-butyl lithium (0.01 M, 1.3 mmol) and 2.0 g of tris(pentafluorophenyl)boron (4.0 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually lowered to 20 degrees Celsius and maintained for 60 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.132 M.

[0051] Embodiment 11

[0052] 7.4 ml of ethyl acetate was added to a 100 ml reactor, and 0.16 ml of phenyl lithium (0.01 M, 1.6 mmol) and 2.4 ml of triethyl boron (1.0 M, 2.4 mmol) were added at room temperature, and stirred well. Afterwards, the temperature was gradually raised to 40 degrees Celsius and maintained for 40 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.160 M.

[0053] Example 12

[0054] 0.6 ml of toluene was added to a 100 ml reactor, and 0.29 ml of lithium silicate (0.031 M, 9.1 mmol) and 9.1 ml of tri-sec-butyl boron (1.0 M, 9.1 mmol) were added at room temperature, and stirred well. Then, the temperature was gradually raised to 60 degrees Celsius and maintained for 10 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.908 M.

[0055] Example 13

[0056] 5.0 ml of diethylene glycol dimethyl ether was added to a 100 ml reactor, and 0.43 ml of sodium silicate (0.0215 M, 9.2 mmol) and 4.6 ml of trioctyl boron (1.0 M, 4.6 mmol) were added at room temperature, and stirred well. Afterwards, the temperature was gradually lowered to -20 degrees Celsius and maintained for 100 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 0.918 M.

[0057] Embodiment 14

[0058] 7.6 ml of ethylene glycol dimethyl ether was added to a 100 ml reactor, and 0.41 ml of potassium silicate (0.024 M, 10.0 mmol) and 1.9 g of triphenylboron (8.0 mmol) were added at room temperature, and stirred well. Afterwards, the temperature was gradually lowered to 0 degrees Celsius and maintained for 80 minutes. A boron-containing alkali metal composition was prepared, wherein the alkali metal concentration was 1.000 M.

[0059] Comparative Example 15 is a comparative example of preparing fluorosilicone rubber using a traditional catalyst.

[0060] 250 g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane was added to a reaction kettle. After maintaining the temperature at 60 degrees Celsius and in a vacuum state for 60 minutes, 23 mg of lithium tert-butoxide was added. After sufficient stirring and dispersion, 1.2 ml of dimethyl sulfoxide was added and polymerized at 60 degrees Celsius for 120 minutes to obtain fluorosilicone rubber.

[0061] Examples 16-27 are examples of using the above catalysts to prepare fluorosilicone rubber.

[0062] The corresponding cyclosiloxane monomers in Table 2 were added into a 500 ml reactor and preheated to the specified polymerization temperature. The specified catalyst was added once and maintained for a given polymerization time. The molecular weight was determined by gel permeation chromatography. The corresponding results of molecular weight distribution and small molecule ring body content are listed in Table 2.

[0063] Table 2

[0064]

[0065] Note: a The catalyst corresponds to the catalyst prepared in the numbered example. The numerical value indicates the amount of catalyst used; b For ease of calculation, the amount of catalyst is measured according to the corresponding alkali metal hydroxide. ; c D3F, D3, D3 Vi 、D3 Ph They correspond to 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, hexamethylcyclotrisiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and 2,4,6-triphenyl-2,4,6-trimethylcyclotrisiloxane, respectively.

[0066] The structure of the fluorosilicone rubber of formula (1) prepared in Examples 15-27, wherein the repeating units without R substituents in Comparative Example 15 and Examples 16-22 are homopolymers of fluorinated siloxanes, the R substituents in Examples 23 and 24 are vinyl, the R substituents in Examples 25 and 26 are phenyl, and the R substituent in Example 27 is methyl.

[0067] Compared with Comparative Example 15, Example 16 is prepared by the fluorosilicone rubber preparation method provided by the present invention, while Comparative Example 15 uses a traditional alkali metal catalyst system. The two are consistent in terms of the ratio of monomer feed amount to alkali metal dosage and polymerization conditions. The polymerization results show that Comparative Example 15 produces up to 12.3% of small molecular weight ring structures. This is mainly due to the fact that during the polymerization process, the alkaline active center triggers the "bite-back" side reaction of the polymer chain, resulting in a decrease in molecular weight and a widening of the molecular weight distribution. The ring structure in the fluorosilicone rubber prepared in Example 16 is only 0.7%, and under the condition of the same catalyst dosage, a high molecular weight polymer can be obtained. This shows that the catalytic system used in Example 16 almost completely inhibits the "bite-back" side reaction commonly seen in the polymerization process triggered by traditional catalysts.

[0068] The obtained fluorosilicone rubbers with similar molecular weights, including Comparative Example 15 and Comparative Example 18, were further subjected to thermogravimetric analysis. The results showed that the temperature of the fluorosilicone rubber prepared in Example 18 at 5% thermal weight loss was 383°C, while that of Comparative Example 15 was 297°C. Both were not subjected to the neutralization process. In Comparative Example 15, due to the residual of the traditional catalyst in the fluorosilicone rubber matrix, the rubber was catalytically degraded during the heat treatment process; while Example 18 still maintained a high stability at a higher temperature.

[0069] The above-mentioned embodiments only show the specific implementation of the present invention and should not be regarded as limiting the scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a fluorosilicone rubber with controllable molecular weight, characterized in that: The following steps are involved: In the first step, 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane and cyclosiloxane monomer are added into a polymerization reactor, heated and vacuumed for dehydration treatment; wherein the amount of cyclosiloxane monomer added accounts for 0.5%-20% of the total weight of the monomer; In the second step, the boron-containing alkaline composition is added into the polymerization reactor. The amount of the boron-containing alkaline composition is 8-500 ppm based on the corresponding alkali metal hydroxide. The polymerization reaction is started by heating to 60-120 degrees Celsius for 10-600 minutes to prepare fluorosilicone rubber.

2. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 1, characterized in that: In the first step, the cyclosiloxane monomer is one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and 2,4,6-triphenyl-2,4,6-trimethylcyclotrisiloxane.

3. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 1, characterized in that: In the first step, the cyclosiloxane monomer is 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane.

4. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 1, characterized in that: In the second step, the boron-containing alkaline composition is prepared by reacting an alkali metal compound with a borane compound.

5. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 4, characterized in that: The preparation method of the boron-containing alkaline composition is as follows: under the protection of inert gas, an alkali metal compound is first added to a preparation kettle, and then a borane compound is slowly added at -40-60 degrees Celsius, and aged for 10-120 minutes to obtain a boron-containing alkaline composition with an alkali metal concentration of 0.1-1.0M.

6. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 5, characterized in that: The molar ratio of the alkali metal compound to the borane compound is 1:(0.2–10); The alkali metal compound is selected from lithium hydride, sodium hydride, potassium hydride, lithium hydroxide, sodium hydroxide, potassium sodium hydroxide, lithium tert-butoxide, sodium tert-butoxide, potassium tert-butoxide, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, phenyl lithium, lithium silicate, sodium silicate, potassium silicate; The borane compound is selected from trimethylboron, triethylboron, tri-n-butylboron, tri-sec-butylboron, trioctylboron, triphenylboron and tri(pentafluorophenyl)boron.

7. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 5, characterized in that: The molar ratio of the alkali metal compound to the borane compound is 1:(1–3); The alkali metal compound is n-butyl lithium; The borane compound is triethylboron or triphenylboron.

8. The method for preparing a fluorosilicone rubber with controllable molecular weight according to claim 5, characterized in that: Before use, the borane compound is mixed with a solvent to form a solution with a concentration of 0.1-1.0M; the solvent includes at least one of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, acetone, 1,4-dioxane, methyl pyrrolidone, phosphazene base P4-t-Bu, tetrahydrofuran, methyl formate, ethyl acetate, toluene, diethylene glycol dimethyl ether, and ethylene glycol dimethyl ether.

9. A fluorosilicone rubber, characterized in that: The fluorosilicone rubber is prepared by the preparation method described in any one of claims 1 to 8, and the structural formula of the fluorosilicone rubber is: Wherein, R is one or more of methyl, phenyl and vinyl.

10. A fluorosilicone rubber according to claim 9, characterized in that: The molecular weight of the fluorosilicone rubber is 0.2-3 million, and the molecular weight distribution is less than 1.50.

Citation Information

Patent Citations

  • Preparation method of wide-temperature-range solvent-resistant fluorosilicone rubber and composition thereof

    CN114381001A

  • Synthetic method of ethyl fluorosilicone rubber

    CN118271619A

  • Aprotic thermo-sensitive polymer as well as synthesis method and application thereof

    CN118325066A

  • process for the preparation of new organometallic compounds of boron

    FR1242703A

  • Lowly migrating curable silicone composition

    JP1999246772A